THE EQUIPMENT OF THE TEDHAK SITEN TRADITION AS A SOURCE FOR CREATING BATIK MOTIFS IN CASUAL CLOTHING - Kusdiyanti, Adilah Raidah; Khoirunnisa, Izzun (Runtas: Jurnal Fesyen dan Wastra Nusantara, 2023)
Fashion creation in this study uses a theme related to Javanese tradition, entitled The Equipment of the Tedhak Siten Tradition as a Source for Creating Batik Motifs in Casual Clothing. This study aims to create a batik motif with the source of equipment ideas of the Tedhak Siten Tradition. It can encourage the preservation of traditions in Indonesia. Therefore, it can create a sense of belonging to and continue to protect cultural heritage. The data is collected from the literature study. The work creation uses a method consisting of exploration, design, and manifestation. Several batik colors are used as a basis in the creation of this fashion work. They are dark brown, light brown, and dark red. The results of this study are four batik motifs by dab coloring technique. Each fashion work is given a title that is considered to have a connection among the character, appearance, and meaning of each style.  Work 1 is entitled "Nawasena", work 2 is entitled "Lavanya", work 3 is entitled "Tapak Kluwung”, and work 4 is entitled "Rumaksara". As a result, this fashion creation can give new shades to the art world, in the form of batik applied in casual clothing.